Advertisements shape our social reality: a study of apple advertisements on promoting PWDs and inclusion - Mokhtar, Aida; Ahmed Elyass Hussain, Souhaila (IIUM Press, International Islamic University Malaysia, 2019)
There are persons with disabilities (PWDs) in each society. The inclusion of PWDs by society, as supported by the United Nation’s sustainable development goals (SDGs), could be encouraged by advertising. Advertising’s influence on one’s worldview is obvious with cultivation theory espousing the phenomenon that prolonged viewing of television could fashion audiences’ worldview by making them believe that the images projected are accurate depictions of reality. PWDs not only nurture compassion within us but provide us with a wealth of opportunities by coming up with inventions that improve their quality of life. These inventions could empower PWDs by giving them greater independence. The global brand, Apple, through its technological devices, gives PWDs jobs, a platform for expression and dignity. Apple has created a series of video advertisements that depict its embrace of inclusion through its technological innovations. The study examines selected Apple’s video advertisements using critical discourse analysis (CDA). The outcome of the study is a framework for brands to use as a guide when incorporating advertising images on the inclusion of PWDs.